STANDAR KOMPETENSI SDM PENYELENGGARA PERKERETAAPIAN MODERN - Nahry, Nahry (Jurnal Ilmiah Teknik Sipil, 2023)
The impact of industry 4.0 is very significant on the use of human resources (HR) due to changes in the technology used, including the presence of modern railways. The development of railway technology in Indonesia is increasing rapidly . HR related to the implementation of modern railways requires additional competence in order to ensure the safety of the transportation system. This study is intended to analyze the need for HR standards of competency in the modern railway sector and evaluate the readiness of the regulator in preparing its human resources. Standards of competenc y are identified using Gap Analysis through benchmarking. Meanwhile, SWOT Analysis is used to evaluate the HR preparation. The results of the analysis show that there are 6 core technologies of modern railways that distinguish modern railways from conventional ones, namely Civil infrastructure and tracks, Rolling Stock, Electric power facilities, Signaling and telecommunication facilities, Operation Control Center, and ICT (Information and Communications Technology) System. The HR competency on modern railway s must be able to support the use of th ese core technolog ies . Eleven main functions of modern railway s HR and their respective competencies are developed. These additional competencies include aspects of safety, ICT, integrated systems, and work ing culture. SWOT analysis result shows that the organization is still weak internally but has opportunities from external parties. The biggest opportunity is the high demand from the industry and operators for certified HR. Its strength is only in terms of the contribution of the Education and Training Institutions which is considerable in meeting market needs. Almost all elements of the Input-Process-Output-Outcomes of Education and Training aspects identified in this study are still weak, although with varying degrees of weakness es . The main weakness from the education and training side is the limited budget and the lack of competence of  regulators and training instructors, as well as the education and training curriculum and syllabus that still need to be prepared. The quality of education and training facilities is also a major weakness. The main weakness in terms of regulation is that the SKKNI is not yet prepared . This study recommends the need to prepare HR that meet the standards of competency, including increasing the role and capacity of education and training institution, the role and preparation of regulators, as well as the need for SKKNI.